If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2(4x + -8) = 6x + 12 + -9x Reorder the terms: 7x + -2(-8 + 4x) = 6x + 12 + -9x 7x + (-8 * -2 + 4x * -2) = 6x + 12 + -9x 7x + (16 + -8x) = 6x + 12 + -9x Reorder the terms: 16 + 7x + -8x = 6x + 12 + -9x Combine like terms: 7x + -8x = -1x 16 + -1x = 6x + 12 + -9x Reorder the terms: 16 + -1x = 12 + 6x + -9x Combine like terms: 6x + -9x = -3x 16 + -1x = 12 + -3x Solving 16 + -1x = 12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 16 + -1x + 3x = 12 + -3x + 3x Combine like terms: -1x + 3x = 2x 16 + 2x = 12 + -3x + 3x Combine like terms: -3x + 3x = 0 16 + 2x = 12 + 0 16 + 2x = 12 Add '-16' to each side of the equation. 16 + -16 + 2x = 12 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 12 + -16 2x = 12 + -16 Combine like terms: 12 + -16 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| W+10=50+25+6 | | 2(w-4)-7=-3(-4w+3)-6w | | X/54=92 | | 0/-107= | | 0/-107=0 | | -31=-4s-3s | | 25=-39+8x | | 10*5/6 | | -7c+4+8=-18 | | -13y=-108 | | -3+5(1-7z)=-16 | | Y/-107=0 | | ?/-107=0 | | 1/6y-5=-16 | | X^2*(x-7)+18*(x-7)= | | -2.6y-17.2=2.5 | | 5x+12=2(2x+4) | | 25-11x= | | -2p+2(-8+2p)= | | X+6=228 | | 12x+(-8)=48 | | X+-44=46 | | -10y+3x=18 | | X/23=51 | | 16=x-(-17) | | =11.94 | | 20x+5(x-4)=21x+4 | | -11w+15=-6+-14w | | f(5)=g(120) | | 3x-15+5x-24=90 | | (11x+33)+(6x-6)=180 | | .75(k+2)=9 |